ILLUSTRATION OF THE PROVISION OF WATER TEPID SPONGE (WTS) ON REDUCING BODY TEMPERATURE IN TODDLERS WITH HYPERTHERMI PROBLEMS IN PANICAN VILLAGE - Adelia, Yora; Sudiarto, Sudiarto; Puspasari , Fida Dyah (PT. Jurnal Center Indonesia Publisher, 2025)
Background: Maintaining children's health is a special concern for parents. Changes in children's health conditions are influenced by changes in weather, one of the symptoms that often occurs in children is fever or hyperthermia. One of the non-pharmacological treatments is by administering Water Tepid Sponge (WTS). Water Tepid Sponge is a combination of warm compress techniques, superficial vascular block compress techniques and wiping techniques. The compression technique is carried out at several points where there are large blood vessels (neck folds, right and left axillary folds, right and left thigh folds) so that vasodilation occurs and then accelerates evaporation and conduction to lower body temperature in children. Objective: To determine the effectiveness of administering Water Tepid Sponge (WTS) to reduce body temperature in toddlers with hyperthermia problems in Panican Village. Method: This study used a descriptive case study with respondents of toddlers with hyperthermia problems. The focus of this case study is the provision of Water Tepid Sponge (WTS) with hyperthermia problems as a nonpharmacological action. This study was conducted in Panican Village for 3 days starting on 23-25 June 2025. Results: After being given Water Tepid Sponge (WTS) for 3 days with 1 meeting within 15-30 minutes using water temperature of 37oC40oC, the child's body temperature decreased, the initial result was 38.7oC and after being given Water Tepid Sponge (WTS) for 3 days, the result was 37.3oC. Conclusion: Providing Water Tepid Sponge (WTS) can reduce body temperature in toddlers with hyperthermia problems in Panican Village.